Implementasi Strategi Pemasaran Produk Lampu Led Pada Pt. Inti Trada Elektro Semarang - Novi Bella Safitri; Maria Augustine Graciafernandy; Moeljono Moeljono (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to analyze the marketing strategy implemented. The marketing strategy is a series of plans as a joint tool to achieve the long-term goals set by the company. The marketing strategy provides direction for each company to control all aspects in order to achieve the company's goals in meeting consumer demands and needs. This research is a qualitative descriptive research. By taking respondents from several sources who are considered appropriate to become resource persons for research. The research results are that the location research has implemented a marketing promotion strategy to increase sales turnover. Sales promotions that are utilized include Personal selling, Sales Promotion and Direct Marketing. The problems faced by the company resulted in fluctuations in sales targets, lack of promotional media aimed at providing information on ongoing promotions and high costs for promotions aimed at increasing consumer brand awareness.